2012
DOI: 10.1159/000337383
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin for Vaginismus Treatment

Abstract: Background/Aims: Vaginismus is characterized by recurrent or persistent involuntary contraction of the perineal muscles surrounding the outer third of the vagina when penile, finger, tampon, or speculum penetration is attempted. Recent results have suggested the use of botulinum toxin for the treatment of vaginismus. Here, we assessed previously published data to evaluate the therapeutic effectiveness of botulinum toxin for vaginismus. Methods: We have carried out a systematic review followed by a meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Porém, seria preciso de mais estudos clínicos randomizados e com grupo controle por placebos para maior comprovação da eficácia. 30 Não obstante, o artigo de Well, Farah (2009) que teve como base a análise de outros cinco estudos em que se foi observado o uso de toxina botulínica para o tratamento do vaginismo, concluiu que o uso de toxina botulínica em comparação ao placebo não houve uma redução significativa da dor em nenhum dos estudos em questão. O estudo também afirma a superioridade de resposta terapêutica quando comparada a fisioterapia isolada à toxina botulínica isolada.…”
Section: Resultsunclassified
“…Porém, seria preciso de mais estudos clínicos randomizados e com grupo controle por placebos para maior comprovação da eficácia. 30 Não obstante, o artigo de Well, Farah (2009) que teve como base a análise de outros cinco estudos em que se foi observado o uso de toxina botulínica para o tratamento do vaginismo, concluiu que o uso de toxina botulínica em comparação ao placebo não houve uma redução significativa da dor em nenhum dos estudos em questão. O estudo também afirma a superioridade de resposta terapêutica quando comparada a fisioterapia isolada à toxina botulínica isolada.…”
Section: Resultsunclassified
“…Meta‐analysis has shown that boutlinum toxin is a useful technique for patients not responding to usual line of treatment 25 …”
Section: Botulinum Toxinmentioning
confidence: 99%
“…For PF trigger points, treatment options include local anaesthetic or Botox A injection. A meta-analysis indicated that there is evidence for the use of Botox in women with vaginismus (76). Local medical therapy such as vaginal diazepam 2.5–10 mg once or twice daily, may be used, but evidence on this is mixed (7779) and systemic absorption is an issue (78).…”
Section: Treatment Of Peripheral Nociceptorsmentioning
confidence: 99%